An evaluation of hands-on activities in terms of learning environment, achievement, and attitudes in grades 4 and 5 - Hilton, Elton (Curtin University, 2006)
A sample of 817 Grade 4-5 mathematics students in the diverse school district of Miami-Dade County Public Schools (MDCPS), Florida, USA was involved in an evaluation of the use of hands-on activities in terms of students' achievement, students' attitudes and students' perceptions of the mathematics classroom environment. Other aims included validating generally-applicable measures of classroom learning environments and students' attitudes to mathematics, and investigating associations between the classroom learning environment and the student outcomes of performance and attitudes. The study was conducted in two phases. Phase 1 had a sample of 442 participants and classroom environment was assessed with scales selected from the My Class Inventory, Questionnaire on Teacher lnteraction and Science Laboratory Environment Inventory. Factor analysis provided a degree of support for the factorial validity and internal consistency reliability (using Cronbach's alpha coefficient) for each of five classroom environment scales. Because of the small number of items per scale (15 items in five scales for the My Class Inventory, 12 items in four scales for the Question on Teacher Interaction and 15 items in five scales for the Science Laboratory Environment Inventory) in Phase I, it was not possible to replicate the a priori factor structure of each instrument scale. Scale reliabilities generally were acceptable. Phase 2, involving a sample of 375 Grades 4 and 5 students in four elementary schools, was necessary because questionnaires in Phase 1 had too few items to enable the researcher to establish satisfactory levels of reliability and validity.The What Is Happening In this Class? (WIHIC) was modified to four scales and 29 questions for use in Phase 2. Factor analysis supported the structure of the WIHIC and internal consistency reliability was satisfactory for two units of analyses, namely, the individual and the class mean. In Phase 1 of the study, differences between an experimental group (that used manipulatives for 60% of the time) and a control group (that used manipulatives for less than 40% of the time), were described in terms of the effect size (magnitude of the difference in standard deviations) and statistical significance for each learning environment, attitude, and achievement scale. Differences between the pretest and posttest for the set of six dependent variables (Student Cohesiveness, Teacher Support, Task Orientation, Cooperation from the WIHIC and Adoption of Mathematical Attitudes and Enjoyment of Mathematics Lessons for the TOMRA) were analyzed in Phase 2 using a MANOVA for repeated measures. Effect sizes were used to describe the magnitude, as distinct from the statistical significance, of prepost changes. In Phase 2, associations between student attitudes and their perceptions of the learning environment were relatively weak for both pretest and posttest data with either the individual or the class mean as the as the unit of analysis. These results were unexpected and are inconsistent with past research, therefore highlighting the need for further research.